2012
DOI: 10.4314/njp.v39i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ knowledge, perception and practice of childhood immunization in Enugu

Abstract: associated with knowledge and acceptance of immunization. These findings are important in the design and implementation of childhood immunization programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 8 publications
8
26
2
Order By: Relevance
“…Despite the fact that greater than half of respondents in this study have mentioned correctly the time when infants should begin and finish vaccination, only 23.8% of mothers correctly knew the objective of immunization (i.e. 'to prevent specific and killer diseases').This is consistent with the response of mothers in rural Nigeria which indicated that only 20.1% [14] and contradicts with another finding in Enugu, Nigeria, 81.2% of respondents mentioned correctly the objective of immunization [15]. The inconsistency between the present participants and the later Nigerian participants may be due to educational status differences in respondents since only 47% of mothers in the present study and 90% of mothers in Nigeria attended secondary school up to higher education.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Despite the fact that greater than half of respondents in this study have mentioned correctly the time when infants should begin and finish vaccination, only 23.8% of mothers correctly knew the objective of immunization (i.e. 'to prevent specific and killer diseases').This is consistent with the response of mothers in rural Nigeria which indicated that only 20.1% [14] and contradicts with another finding in Enugu, Nigeria, 81.2% of respondents mentioned correctly the objective of immunization [15]. The inconsistency between the present participants and the later Nigerian participants may be due to educational status differences in respondents since only 47% of mothers in the present study and 90% of mothers in Nigeria attended secondary school up to higher education.…”
Section: Discussioncontrasting
confidence: 50%
“…Accordingly, Infants in Health Centers at Addis Ababa, Ethiopia literate mothers attending grade 1-8 th were about two times (AOR= 1.781, 95% CI: 1.035, 3.065) more likely to have good knowledge of immunization than illiterate mothers. Similarly, other study findings conducted in United Arab Emirates and Enugu (Nigeria) mothers attending secondary or higher educational status was significantly associated with good knowledge and acceptance of immunization [15,9]. In addition to literacy status, mothers who had infants aged from 3-9 months and 9-12 months old were about two times more likely to have good knowledge of immunization than mothers who had infants below one month.…”
Section: Discussionmentioning
confidence: 94%
“…Childhood vaccination has contributed to major global reductions in morbidity and mortality [1,2] and is considered to be the most successful public health intervention in terms of number of deaths averted per year [3,4]. However, the World Health Organization (WHO) and the United Nations Children’s Fund (UNICEF) estimate that 1.5 million children worldwide continue to die from vaccine-preventable diseases every year because of sub-optimal vaccination coverage [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed in another study by Hamid [12], that many of the mothers did not know that tuberculosis is prevented by BCG vaccines [20]. In contrast to Tagbo et al [21] mothers had a good knowledge of child immunization. They knew that children need to be immunized and 89.9% knew the contents of the vaccines are substances that prevent the killer diseases.…”
Section: Discussionmentioning
confidence: 55%
“…They knew that children need to be immunized and 89.9% knew the contents of the vaccines are substances that prevent the killer diseases. The majority of mothers (80.9%) stated that they will continue with immunization even though the child suffered an adverse effect [21].…”
Section: Discussionmentioning
confidence: 99%